1999
DOI: 10.1044/jslhr.4204.785
|View full text |Cite
|
Sign up to set email alerts
|

Older Adult Performance on the Communication Profile for the Hearing Impaired

Abstract: Gender difference in auditory function with age is well documented. However, little is known about the influence of interacting sensory, psycho-social, and economic variables on adjustment to hearing loss. Adjustment to acquired, mild-to-moderate hearing loss by advantaged older women and men was examined using the Communication Profile for the Hearing Impaired (CPHI) (Demorest & Erdman, 1987). Correlational analyses revealed relationships between scales to be similar for women and men. Controlling for socio-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
57
1
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 25 publications
4
57
1
2
Order By: Relevance
“…Acitelli (2002) noted that studies have consistently demonstrated that variables emphasizing connections between partners are more important to the well-being and relationship satisfaction of wives than of husbands. These and other studies suggest that communication may be more important for women in marriage than for men (Garstecki & Erler, 1999); if this is so, one would expect that the extent to which vision impairment makes communication more difficult would have a more negative impact on wives than husbands.…”
mentioning
confidence: 99%
“…Acitelli (2002) noted that studies have consistently demonstrated that variables emphasizing connections between partners are more important to the well-being and relationship satisfaction of wives than of husbands. These and other studies suggest that communication may be more important for women in marriage than for men (Garstecki & Erler, 1999); if this is so, one would expect that the extent to which vision impairment makes communication more difficult would have a more negative impact on wives than husbands.…”
mentioning
confidence: 99%
“…In this case, hearing loss stigma is a mediating factor and is part of the causal pathway between problems with a health related activity and the engagement in a life situation. Numerous studies have identified such environmental factors, such as hearing aids (Mulrow et al, 1990), the acoustical environment (Gatehouse & Noble, 2004), hearing loss stigma (HĂ©tu, 1996), and applied coping strategies (Garstecki & Erler, 1999). Consequently, failing to map such factors would yield an incomplete understanding of a person's functioning and personal situation.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, a study using data from the Australian Longitudinal Study of Aging reported that perceptual speed for husbands predicted subsequent perceptual speed decline for wives 1 year later but reported no evidence for the opposite effect [7] . Studies of older couples involving affective transmissions and conditions such as hearing loss and cognitive problems on health and well-being have also reported stronger impacts on wives than husbands [8][9][10] . Rationales for wives include greater importance of communication in marriage [8,10] and greater importance of spouse relationships for older wives [11] .…”
Section: Introductionmentioning
confidence: 99%
“…Studies of older couples involving affective transmissions and conditions such as hearing loss and cognitive problems on health and well-being have also reported stronger impacts on wives than husbands [8][9][10] . Rationales for wives include greater importance of communication in marriage [8,10] and greater importance of spouse relationships for older wives [11] . We only found 2 studies with the opposite unidirectional relationship.…”
Section: Introductionmentioning
confidence: 99%